Book collecting : a modern guide - 4 0 16; 1935- Peters, Jean; 5 (New York : R. R. Bowker, 1977)
Discusses the procedures and techniques of traditional book collecting.
Includes bibliographical references (p. 209-271) and index.
Library Journal
Adult;Adult
Keywords: 2 -- 0; 6; Book collecting. -- 20; 20; 2